Novel ETFDH mutation and imaging findings in an adult with glutaric aciduria type II. Issue 3 (31st January 2014) - Rosenbohm, Angela; Süssmuth, Sigurd D.; Kassubek, Jan; Müller, Hans‐Peter; Pontes, Christina; Abicht, Angela; Bulst, Stefanie; Ludolph, Albert C.; Pinkhardt, Elmar
ABSTRACT Introduction: Glutaric aciduria type II (GAII) is a rare autosomal recessive disorder with variable clinical course. The disorder is caused by a defect in the mitochondrial electron transfer flavoprotein or the electron transfer flavoprotein dehydrogenase (ETFDH). Methods: We performed clinical characterization, brain and whole body MRI, muscle histopathology, and genetic analysis of the ETFDH gene in a young woman. Results: She presented with rhabdomyolysis and severe quadriparesis. We identified a novel homozygous missense mutation in ETFDH (c.1544G>T, p.Ser515Ile). Body fat MRI revealed a large amount of subcutaneous fat but no increase in visceral fat despite steatosis of liver and muscle. Diffusion tensor imaging (DTI) of cerebral MRI revealed reduced directionality of the white matter tracts. Histopathological findings showed lipid storage myopathy. Conclusions: In this study, we highlight diagnostic clues and body fat MRI in this rare metabolic disorder. Muscle Nerve49:446–450, 2013